BLACK WOMEN EXERCISERS, ASIAN WOMEN ARTISTS, WHITE WOMEN DATERS, AND LATINA LESBIANS: HOW RACE AND GENDER MATTER IN FACEBOOK GROUPS - Korn, Jenny Ungbha (AoIR Selected Papers of Internet Research, 2014)
In this paper, I contribute to the “new cultural politics of difference” by focusing on modern, organic representations of race and gender on the Internet (West, 1993). Facebook groups reflect a contemporary way for users to demonstrate membership in cultural groups that are salient to them, including ones based on race and gender. Internet-based displays of intersectional membership via Facebook groups reflect the ongoing significance of race with gender. Together, race and gender may be understood as part of “culture” or “the sum of the available descriptions through which societies make sense of and reflect their common experiences” (Hall, 1980: 59).